The Workforce Investment and Opportunity Act: New Policy Developments and Persistent Issues. Issue 155 (19th September 2017) - Jacobson, Erik
Abstract: This chapter reviews how the impact of WIOA on adult education provision in the United States may be limited because of persistent structural problems within adult education policy and practice.